Menggugat penguasa : ing ngarso ngumbar angkoro - Mashad, Dhurorudin (Ciracas, Jakarta : Erlangga, 1999)
Political conditions in Indonesia during the transition period post the Soeharto government
Includes bibliographical references (p. [132]-133) and index
In Indonesian
Keywords: Indonesia -- Politics and government -- 1998-